Calculation method of information dissemination based on information entropy in public internet - Panpan LI; Zhengxia XIE; Zengkai WANG; Rui JIN (Dianxin kexue)
A method of how to calculate the influence of information dissemination based on the maximum entropy theory was presented, which aimed at evaluating the impacts of the information dissemination in the open internet environment.Firstly, the influential factors of the information dissemination were analyzed.Then, the factors that have high correlation with the calculation of information dissemination were selected by the principle of “Occam’s Razor”, based on Shannon's information entropy theory.Finally, the method of computing the influence of information dissemination was proposed based on the information entropy theory.The effectiveness of the proposed method was validated by the experiments of analyzing the influence of the information dissemination of academic paper citations and hot public opinion events.The experiments show that the proposed method is of great significance for investigating the influence of information dissemination and the extent of impacts on the audience as well as the trends of information evolution in the open internet environment.